Utility of axial magnetic resonance images for detecting meniscal ramp lesions associated with anterior cruciate ligament injuries - Tomonori Kinugasa; Hirotaka Mutsuzaki; Yu Taniguchi; Yuki Sato; Arata Watanabe; Kotaro Ikeda (Elsevier, 2022)
Background: Ramp lesions (RLs), associated with anterior cruciate ligament (ACL) injuries, should be repaired to ensure postoperative knee stability. However, it is difficult to identify all RLs before surgery using conventional sagittal magnetic resonance (MR) images and arthroscopy from the anterior, medial, and lateral portals that are usually used during ACL reconstruction. We report the effectiveness of axial images for detecting RL. Methods: From January 2018, a total of 316 knees underwent primary ACL reconstruction with preoperative magnetic resonance imaging (MRI) examination at our hospital. Among these, 149 knees, which required meniscal suturing at the same time, were retrospectively investigated. This study evaluated 22 knees with confirmed RLs around the posterior horn of the medial meniscus. The effectiveness of the preoperative sagittal and axial MR images for detecting RL was assessed. With the MR image, a three-dimensional double-echo steady-state image with a flip angle of 25° was reconstructed into the sagittal and axial planes, respectively. Reconstructed images with 3-mm slices for sagittal slices and 1-mm slices for axial sections were used. The diagnosis was made based on the presence of RL (RL was present, RL may be present, and RL was not present) by four knee surgeons with more than 10 years of experience. Results: Approximately 53% of knee cases were diagnosed with RLs using sagittal images. Meanwhile, a diagnosis was achieved using axial images in 89% of cases. Conclusion: Axial MRI may be superior in detecting RLs.